Indigenous People, Local Belief, and Its Protection in Indonesia: Case of Asmat Tribe Belief (Law Research Review Quarterly, 2021)
Indonesia is a country consisting of many islands and many various tribes, language, customs or what we often call culture. The cultural diversity found in Indonesia is a proof that Indonesia is a country rich in culture. We cannot deny that regional culture is a first factor in the establishment of a more global culture, which we usually call national culture. So, on the basis of that all forms of a regional culture will greatly affect the national culture, and national culture come from regional culture, will greatly affect the local culture. Culture is a very valuable wealth because in addition to the characteristic of a region also be a symbol of the personality of a nation or region. Because culture is a wealth and characteristic of a region, so maintaining, preserving, and preserving culture is an obligation of every individual, in other words culture is a wealth that must be maintained and preserved by each tribe. In this discussion is expected to know about the customary law in the tribe Asmat by looking at various aspects. This paper is intended to analyze the local belief in Indonesia especially Asmat Tribe Belief and the legal protection. The paper analyzes the legal framework for the protection of local beliefs in Indonesia